Use of non conventional water resources in irrigated agriculture - El Gamal F. (Water saving in Mediterranean agriculture and future research needs [Vol. 2], 2007)
The use of non-conventional water has a multidisciplinary nature with inter-linkage with environment, health, industry, agriculture and water resource policy. In this regard, significant challenges still remain in the areas of technological, managerial and policy innovation and adaptation, human resources development, information transfer and social and environmental considerations. Sustainability and success of non conventional water uses depend on sound implementation and management. During the planning and management phases, the ecological, social and economic aspects should be considered in order to assure social and economic viability of any reuse activities. Further research is necessary to develop general guide lines, setting up a universal strategy and use systemic indicators for assessing, monitoring and evaluating the sustainability of non conventional water reuse in the Mediterranean region. For sustainable and safe use of non conventional water, it is needed to provide the decision maker and the users with a concrete and very clear answer on how agriculture can make use of non conventional water resources in a way that is technically sound, economically viable and environmentally non-degrading.
Proceedings of the International Conference WASAMED Project (EU contract ICA3-CT-2002-10013), 2007/02/14-17, Valenzano (Italy)